Model szkoły w świetle pedagogiki chrześcijańskiej Instytutu Edukacji Narodowej - Śliwerski, Bogusław (Annales. Etyka w Życiu Gospodarczym, 2009)
The paper focuses on the role of the Institute of National Education set up in 1997 within Radio Maryja, an intellectual formation chosen by right-wing politicians. The Institute is interested in reforming education; it also questions the existing assumptions of education transformations relating to the model of the moral-shaping school or the societal role of pedagogical sciences. It engages in a variety of education forms, including National Education School, the Academy of Ethical Upbringing, the Academy of Social Abilities, the Summer School of Polish Culture, professional development classes as well as symposia and popular scientific lectures. The Institute is present in publishing. Moreover, it is responsible for organizing summer holidays and pilgrimages; it co-operates with the Redemptorists during retreat meetings. Yet another branch of the Institute is Feliks Koneczny Thought Club and the Maksymilian Kolbe School of Journalism. In the light of its prominence, the discussed movement should be able to contribute significantly to the debate on the education transformation.